2021
DOI: 10.1111/tbj.14301
|View full text |Cite
|
Sign up to set email alerts
|

Superficial angiomyxoma of the breast in a 16‐year‐old girl without carney’s complex: A case report

Abstract: Superficial angiomyxoma (SA) is a rare benign soft‐tissue tumor, arising sporadically or as the earliest manifestation of Carney's complex. When it arises sporadically, the breast is infrequently involved with only few cases reported in the literature. Key imaging findings include T2 signal hyperintensity on MRI and hypervascularity. In this study, we report the clinical, radiological, surgical, and histopathologic findings of a case of sporadic SA of the breast in a 16‐year‐old girl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…On immunohistochemistry, the tumor was positive for CD34 and ERG, while EMA, SMA, S-100, Desmin, ER, and PR were negative. Histological and immunohistochemistry ndings were in line with the prior reports (5)(6)(7)(8)(9)(10)(11).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…On immunohistochemistry, the tumor was positive for CD34 and ERG, while EMA, SMA, S-100, Desmin, ER, and PR were negative. Histological and immunohistochemistry ndings were in line with the prior reports (5)(6)(7)(8)(9)(10)(11).…”
Section: Discussionsupporting
confidence: 90%
“…Kumar et al ( 9) reported a case with contrast-enhanced computed tomography and showing a predominantly necrotic mass in the right breast/subcutaneous plane of chest wall with no underlying muscle in ltration. And Dubin et al (11) reported a case demonstrating with a vascular, hypoechoic mass with partially circumscribed margins on ultrasonography and an enhancing, T1 hypoinense, markedly T2 hyperintense mass on chest MRI, which were in line with our ndings. And marked T2 hyperintensity on MRI which re ect the high-water content and myxoid matrix have been considered the typical imaging feature of myxoid soft-tissue lesions (12).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…There is scant literature on the radiologic appearance of SAM (9)(10)(11). The best imaging modality for evaluating SAM is magnetic resonance imaging because of its excellent tissue contrast.…”
Section: Discussionmentioning
confidence: 99%
“…4,12,13 Mutations or large deletions in PRKAR1A, or loss of PRKAR1A by immunohistochemistry, are found in both syndromic and sporadic forms of these tumor types. 4,10,11,13,14 Despite Carney and Toorkey's original description, these lesions, when occurring in breast, have not been well-characterized in subsequent literature, and there are just a few case reports of similar myxoid lesions arising in the nipple and breast, [15][16][17][18][19] described under various diagnostic terms such as myxoma of breast, nodular mucinosis, nodular/lobular myxoid change, and myxoid fibroadenoma . In our clinical practice, we have encountered cases of "superficial" angiomyxoma arising in various locations within the breast region, including in the dermis and/or subcutis, or deeper within breast parenchyma.…”
mentioning
confidence: 99%